Soy Sauce in Sundanese Family Cuisine in Rural Areas - Nashwa Fadya Nurinsani; Hardian Eko Nurseto (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study discusses sweet soy sauce in Sundanese family cuisine in rural areas, focusing on its diverse uses, gastronomic preferences, and its place in the culinary traditions of Cikembang Village. This study uses a mix of quantitative and qualitative methods, with quantitative methods helping to determine the frequency of use, while interviews and observations provide in-depth information. The results of the study show that sweet soy sauce is widely used in foods prepared using wet heat and semi-dry techniques. The foods prepared are not only everyday dishes but also foods that are only available at certain times, such as celebrations and New Year. The preference for sweet soy sauce among Sundanese families is influenced by geography, availability, price, size, and culture. Meanwhile, for culinary businesses, the preferences are influenced by price and size